Effect of age and spacing on biomass production in forest plantations - Elder Eloy; Dimas Agostinho da Silva; Braulio Otomar Caron; Elvis Felipe Elli; Felipe Schwerz (Revista Árvore, 2018)
ABSTRACT The aim of this study was to determine the effect of age and plant spacing on biomass production of four forestry tree species: Acacia mearnsii De Wild, Eucalyptus grandis W. Hill ex Maiden, Mimosa scabrella Benth, and Ateleia glazioviana Baill. The following spacings of plants at the ages of 1, 3, and 5 years after planting were considered: 2.0 × 1.0 m, 2.0 × 1.5 m, 3.0 × 1.0 m, and 3.0 × 1.5 m. The study was installed in randomized complete block design. Biomass was determined by weighing different components of the trees after harvesting. Plant spacing affected biomass production of forestry trees at different ages after planting. Dense spacings produced larger quantities of biomass than less dense spacing. The tree species differed in biomass production: Eucalyptus grandis produced the largest quantity (325.1 t ha-1), followed by Acacia mearnsii (239.3 t ha-1), Mimosa scabrella (53.4 t ha-1), and Ateleia glazioviana (32.1 t ha-1). Wood biomass represented the biomass component with the largest production over time, which showed an increasing proportion throughout the age groups, followed branch, leaf, and bark biomass.